Peace building Berbasis Komunitas Lokal dalam Penyelesaian Konflik Antaragama: Kontribusi Yayasan Lintas Agama di Jawa Timur - Setianingsih, Dwi (The Sociology of Islam, 2021)
This article attempts to describe how ethnic and religious conflicts in Indonesia can be resolved through a local community-based peacebuilding approach. The phenomenon in Indonesia shows that conflicts are ethnic and religious influenced arise as a response to the political, social and economic dynamics that have participated in the social life of the community. Learning from experience in Pacet East Java, inter-religious conflicts can be resolved through a peacebuilding approach by maximizing local potential and the work of local communities initiated by the East Java Interfaith Foundation (YLA). The idea developed is that community-based peacebuilding is part of the implementation of peace concepts in the form of concrete work in the community in resolving ethnic and religious conflicts at the local level. The findings from this article show that the implementation of local community-based peacebuilding development that toward the basic needs of the community and through local wisdom is very effective in resolving inter-religious conflicts. In addition, to build interaction between various parties in the community in the short term, while in the long term a more mature and detailed concept is needed, so that the level of success can be measured.